2016
DOI: 10.1080/15592294.2016.1214781
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and epigenetic interactions of novel DNA hypomethylating agent guadecitabine (SGI-110) in preclinical models of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a deadly malignancy characterized at the epigenetic level by global DNA hypomethylation and focal hypermethylation on the promoter of tumor suppressor genes. In most cases it develops on a background of liver steatohepatitis, fibrosis, and cirrhosis. Guadecitabine (SGI-110) is a second-generation hypomethylating agent, which inhibits DNA methyltransferases. Guadecitabine is formulated as a dinucleotide of decitabine and deoxyguanosine that is resistant to cytidine deaminase (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 44 publications
1
62
0
Order By: Relevance
“…In well‐differentiated tumors, cells resembled organized hepatocytes, and almost all nuclei were positive for macroH2A1 (Fig. B, left panel), as reported . We then confirmed that the observed decreases in macroH2A1 expression were not restricted to a specific isoform: both alternatively spliced macroH2A1 variants, macroH2A1.1 and macroH2A1.2, were significantly lower at the mRNA and protein levels in poorly differentiated versus well‐differentiated HCC, as assessed by quantitative PCR and immunoblotting (Fig.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In well‐differentiated tumors, cells resembled organized hepatocytes, and almost all nuclei were positive for macroH2A1 (Fig. B, left panel), as reported . We then confirmed that the observed decreases in macroH2A1 expression were not restricted to a specific isoform: both alternatively spliced macroH2A1 variants, macroH2A1.1 and macroH2A1.2, were significantly lower at the mRNA and protein levels in poorly differentiated versus well‐differentiated HCC, as assessed by quantitative PCR and immunoblotting (Fig.…”
Section: Resultssupporting
confidence: 85%
“…Increased levels of macroH2A1 expression mark differentiated human HCC . Here, we examined whether macroH2A1 expression varies between human HCCs with different degrees of stem‐like characteristics (differentiation, aggressiveness, refractoriness to chemotherapy, and high recurrence).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This synergistic effect results in the suppression of a subset of tumour suppressor genes (CDKN2A, DLEC1, and RUNX2) and enhanced HCC cell growth in Hep G2 and Huh-7. Treatment with DNA hypomethylating agent guadecitabine reversed this effect leading to inhibition of HCC cell growth [62]. EZH2 is an important component of PRC2 that interacts with EED and SUZ12 to establish trimethylation of H3K27 (H3K27me3) leading to tumour initiation and progression [63, 64].…”
Section: Nonviral-induced Hcc Hepatoepigenetic Aberrationsmentioning
confidence: 99%